Pengembangan Multimedia Interaktif Berbasis Problem Based Learning (PBL) Berbantuan Articulate Storyline 3 pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Azmi, Nur Kholila; Adrias, Adrias; Engreini, Syofianti; Hamimah, Hamimah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop valid, practical, and effective interactive multimedia based on Problem-Based Learning (PBL) assisted by Articulate Storyline 3 for IPAS learning in Grade IV Elementary School. The research used the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, validation sheets, teacher and student response questionnaires, as well as pre-tests and post-tests. The research subjects consisted of SDN 22 Koto Lalang, SDN 19 Baringin, and SDN 15 Koto Lalang. The validation results showed that the interactive multimedia was in the highly valid category with an average score of 94.88%. The practicality test also showed highly practical results, with teacher responses ranging from 95.71% to 98.57% and student responses ranging from 86.37% to 93.20%. The effectiveness test based on the N-Gain calculation showed an increase in learning outcomes in the three schools, with scores of 79.48%, 80.31%, and 79.54% respectively, which are classified as effective. Thus, the PBL-based interactive multimedia developed using Articulate Storyline 3 is suitable for use as an IPAS learning medium in Grade IV.